Would I lie to you : a Gossip Girl novel - Von Ziegesar, Cecily (New York : Little, Brown, 2006)
Follows of the lives of Blair, Serena, and their wealthy Manhattan friends during the summer following high school graduation.
Keywords: Interpersonal relations -- Juvenile fiction; Wealth -- Juvenile fiction; Interpersonal relations -- Fiction; Wealth -- Fiction; New York (N.Y.) -- Juvenile fiction; Hamptons (N.Y.) -- Juvenile fiction; New York (N.Y.) -- Fiction; Hamptons (N.Y.) -- Fiction